Acute-onset amnesia: transient global amnesia and other causes. Issue 3 (3rd May 2022) - Miller, Thomas D; Butler, Christopher R
Abstract : Acute-onset amnesia is a dramatic neurological presentation that can cause considerable concern to both patient and clinician. The patient typically presents with an inability not only to retain new memories but also to access previously acquired memories, suggesting disturbance of hippocampal function. Transient global amnesia (TGA) is the most common cause of acute-onset amnesia, and is characterised by a profound anterograde and retrograde amnesia that typically lasts for up to 24 hours. Although TGA has a strikingly stereotypical presentation, it can be challenging to distinguish from other causes of acute-onset amnesia, including posterior circulation strokes, transient epileptic amnesia, psychogenic amnesia, post-traumatic amnesia, and toxic/drug-related amnesia. Here, we describe the general approach to the patient with acute amnesia; summarise the clinical and neuropsychological differences between the potential causes; and, provide practical recommendations to aid diagnosis and management of acute amnesia. Regardless of cause and the dramatic presentation, non-ischaemic acute-onset amnesia generally has a favourable prognosis.